Criticize the Policy of Addressing Overcapacity in Correctional Institutions as Part of the Crime Prevention Policy - Ainun Aulia Haq; Hesti Septianita (Eduvest - Journal of Universal Studies, 2026)
The correctional system constitutes an important part of the criminal justice system in Indonesia. The Correctional Institution System is an institution within the criminal justice subsystem that serves as a rehabilitation center for inmates and juvenile offenders in Indonesia. This research aims to critically analyze current policies addressing prison overcapacity and to propose an integrated crime prevention strategy as a fundamental solution, thereby shifting from a retributive to a restorative and rehabilitative paradigm. This study employs a qualitative research method with a normative legal approach, presented descriptively. The normative legal approach entails legal research conducted by examining library materials or secondary data as the basis for analysis through a search of regulations and literature related to the issues under study. The results indicate that addressing overcrowding in prisons cannot rely solely on physical construction or the granting of remissions; rather, it requires a systemic transformation of perspectives, policies, and the national criminal legal system to render it more fair, integrative, and humane. Finally, addressing overcrowding is not solely the responsibility of the Ministry of Law and Human Rights but a cross-sectoral national agenda. All ministries and agencies must align their vision to recognize that criminal justice serves not merely as a tool for state retribution but to foster sustainable social order and justice. Therefore, a progressive, participatory, and systemic legal approach is necessary to prevent the overcrowding crisis from perpetuating a cycle of failed policies.